Evaluation of the aphrodisiac potential of rice field eel, monopterus albus extracts in male mice - Zulkefli, Nor Intan Fazleen; Hashim, Ridzwan (Penerbit Universiti Kebangsaan Malaysia, 2017)
Rice field eel, Monopterus albus, is widely consumed by the local people as a source of traditional medicine. Therefore, this study was conducted to evaluate the M. albus aqueous and lipid extracts as an aphrodisiac based on the mounting behaviour and mating assessment. The doses used for both extracts were 50, 100 and 200 mg/kg. Negative control mice received 0.9% saline while positive control received 5 mg/kg Sildenafil citrate or Viagra®. The observation was carried out for 1 h after administration of the respective doses of the extracts. Male mice treated with the different doses of lipid extract showed substantial mounting behaviour. Meanwhile, only male mice treated with 200 mg/kg aqueous extract displayed aphrodisiac property which was similar to 200 mg/kg lipid dose. As both extracts produced higher number of mounting than Sildenafil citrate at 1st h of observation, this indicated that they are as competent as Sildenafil citrate. In conclusion, this study provides evidence that M. albus could be used as an alternative source for male sexual activity.